Characterization of Blend Films of Chitosan/Poly-Saccharide from Grifola frondosa - Huang, Aibin; Yang, Xuejia; Liu, Caifeng; Chen, Bihui (Asian Journal of Chemistry, 2011)
Films were prepared by the casting method using chitosan (CH) and polysaccharide from Grifola frondosa (GF) in different ratios. The concentration of GF ranged from 0-80 % (v/v). Films were evaluated for mechanical and swelling properties. Water vapour transmission rate and oxygen permeability of the films were also investigated. The water vapour transmission rate did not change significantly upon addition of GF. Films containing 20 % (v/v) GF showed very low oxygen permeability, good tensile and puncture strength. It indicated that blend films owned better properties against degradation in vitro than that of chitosan film. The antimicrobial activity of films containing 20 % (v/v) GF was comparable to CH films against Staphylococcus aureus (MRSA) (ATCC 25923). Composite films obtained from CH and GF may be potentially applied to a broader field in wound dressings.